Sociodemographic, Clinical, and Epidemiological Characteristics of Older Adults with Cognitive Impairment - Naifi Hierrezuelo Rojas; Alfredo Hernández Magdariaga; Rolando Bonal Ruiz (RHS Revista Humanismo y Sociedad)
Aging leads to deterioration of the functional capacities and increases individuals’ vulnerability. This descriptive, cross-sectional study characterized older adults with cognitive impairment from the Basic Work Group No. 2 in the Ramón López Peña University Hospital, in Santiago de Cuba, between January 2022 and January 2023. The study included a sample of 124 older adults who met the established inclusion criteria. Sociodemographic and clinical variables—such as age, sex, occupation, educational level, and independence to conduct daily life activities—were analyzed using descriptive statistics techniques. The results showed that cognitive impairments were most prevalent among individuals aged 60 to 69 (49.9%), women (55.6%), married individuals (41.9%), those with higher education (41.9%), and retirees (50.8%). The most common risk factors were a sedentary lifestyle (64.5%) and malnutrition (55.6%), while high blood pressure was the most observed comorbidity (41.9%). The findings showed that cognitive impairment was particularly more prevalent among married and retired women. Although the participants’ independence in basic activities in their daily lives remained significantly unaffected by their cognitive impairment, notable difficulties were observed in instrumental activities such as washing clothes, using the telephone and managing finances.